3D bioprinting of skin: a state-of-the-art review on modelling, materials, and processes. (7th September 2016) - Vijayavenkataraman, S; Lu, W F; Fuh, J Y H
Abstract: The skin is the largest organ of the body, having a complex multi-layered structure and guards the underlying muscles, bones, ligaments, and internal organs. It serves as the first line of defence to any external stimuli, hence it is the most vulnerable to injury and warrants the need for rapid and reliable regeneration methods. Tissue engineered skin substitutes help overcome the limitations of traditional skin treatment methods, in terms of technology, time, and cost. While there is commendable progress in the treating of superficial wounds and injuries with skin substitutes, treatment of full-thickness injuries, especially with third or fourth degree burns, still looks murkier. Engineering multi-layer skin architecture, conforming to the native skin structure is a tougher goal to achieve with the current tissue engineering methods, if not impossible, restoring all the functions of the native skin. The testing of drugs and cosmetics is another area, where engineered skins are very much needed, with bans being imposed on product testing on animals. Given this greater need, 3D bioprinting is a promising technology that can achieve rapid and reliable production of biomimetic cellular skin substitutes, satisfying both clinical and industrial needs. This paper reviews all aspects related to the 3D bioprinting of skin, right from imaging the injury site, 3D model creation, biomaterials that are used and their suitability, types of cells and their functions, actual bioprinting technologies, along with the challenges and future prospects.